LINGKUNGAN HIJAU: Strategi Penyelesaian Masalah Sampah - Sulistina, Erine (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The waste problem has become one of the most pressing environmental challenges worldwide. Population growth and increasing consumption have led to a significant increase in waste production, which has a negative impact on the environment and human well-being. Therefore, this research aims to identify and analyze effective and sustainable waste problem solving strategies. This research uses a qualitative approach with a literature review method. Literature analysis is used to understand the causes and impacts of waste problems and strategies for solving them. The research results show that effective waste reduction strategies involve a sustainable approach that includes source reduction, efficient collection, environmentally friendly processing, and public education. The use of modern technology such as recycling and sophisticated waste processing also makes a significant contribution to reducing the amount of waste that ends up in landfills. In addition, increasing public awareness and active participation in waste reduction programs are key factors in the success of this strategy.